Evaluation of Relative Afferent Pupillary Defect Using RAPDx Device in Patients with Optic Nerve Disease. (3rd May 2016) - Satou, Tsukasa; Ishikawa, Hitoshi; Asakawa, Ken; Goseki, Toshiaki; Niida, Takahiro; Shimizu, Kimiya
ABSTRACT: We previously reported the standard values of the amplitude and latency scores in the RAPDx device for evaluating relative afferent pupillary defect (RAPD). Here, we evaluated RAPD in patients with optic nerve disease by using these standard values. Twenty-eight patients with current or previous optic nerve disease were enrolled in this study. Additionally, the data of 84 healthy subjects from our previous report were used as control data. We measured the amplitude and latency scores using RAPDx. We then compared their mean values and the percentages of individuals with standard values within a certain range between the optic nerve disease group and healthy group. Additionally, we evaluated their correlation with visual acuity and the critical flicker fusion frequency in the optic nerve disease group. Both parameters were significantly higher in the optic nerve disease group than in the control group ( p < 0.0001). The detection rate of RAPD when using the standard value of amplitude score was 75%. Additionally, both parameters showed a significant correlation with laterality-based differences in visual acuity and critical flicker fusion frequency values in the optic nerve disease group ( r = 0.59–0.75, p < 0.001). The amplitude and latency scores determined using RAPDx are useful in evaluating RAPD, particularly the standard value of the amplitude score.